2018
DOI: 10.3390/s18113670
|View full text |Cite
|
Sign up to set email alerts
|

Application of Computational Intelligence Methods for the Automated Identification of Paper-Ink Samples Based on LIBS

Abstract: Laser-induced breakdown spectroscopy (LIBS) is an important analysis technique with applications in many industrial branches and fields of scientific research. Nowadays, the advantages of LIBS are impaired by the main drawback in the interpretation of obtained spectra and identification of observed spectral lines. This procedure is highly time-consuming since it is essentially based on the comparison of lines present in the spectrum with the literature database. This paper proposes the use of various computati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Laser‐induced breakdown spectroscopy (LIBS) and Raman spectroscopy are two famous spectral techniques because of their advantages in rapid, online, and in‐site detection. [ 1,2 ] As a new elemental detection method, LIBS has been used in identification of many kinds of substance with chemometrics, for instance, biomedical samples, [ 3–5 ] forensic evidences, [ 6–9 ] explosives, [ 10 ] plants, [ 11 ] alloy, [ 12 ] ore, [ 13 ] nutrient food, [ 14–16 ] and pathogenic microorganisms. [ 17 ] However, for substances with the same elemental composition, the feature line wavelengths are always similar.…”
Section: Introductionmentioning
confidence: 99%
“…Laser‐induced breakdown spectroscopy (LIBS) and Raman spectroscopy are two famous spectral techniques because of their advantages in rapid, online, and in‐site detection. [ 1,2 ] As a new elemental detection method, LIBS has been used in identification of many kinds of substance with chemometrics, for instance, biomedical samples, [ 3–5 ] forensic evidences, [ 6–9 ] explosives, [ 10 ] plants, [ 11 ] alloy, [ 12 ] ore, [ 13 ] nutrient food, [ 14–16 ] and pathogenic microorganisms. [ 17 ] However, for substances with the same elemental composition, the feature line wavelengths are always similar.…”
Section: Introductionmentioning
confidence: 99%
“…Similar conclusions were reached by Trejos et al, who reported discrimination by LIBS among black gel inks and ballpoint pen inks between 96% and 99% [ 8 ]. Other research papers published about pen ink analysis by using LIBS [ 26 , 27 , 28 , 29 ] reported that the discrimination power depends on the experimental conditions and the data analysis procedure. LIBS analysis of printing inks also showed a high classification rate, which was 100% for black toners and 97.8% for black inks from inkjet printers [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ksiazec et al [21] used a machine learning approach to detect Hepatocellular Carcinoma using physiological features. Rzecki et al [22,23] proposed the computational intelligence methods for person recognition using biometric features and used the same method for the automated identification of paper-ink samples through laser-induced breakdown spectroscopy.…”
Section: Introductionmentioning
confidence: 99%